2016
DOI: 10.2196/jmir.5935
|View full text |Cite
|
Sign up to set email alerts
|

Possible Biases of Researchers’ Attitudes Toward Video Games: Publication Trends Analysis of the Medical Literature (1980–2013)

Abstract: BackgroundThe study of video games is expanding, and so is the debate regarding their possible positive and deleterious effects. As controversies continue, several researchers have expressed their concerns about substantial biases existing in the field, which might lead to the creation of a skewed picture, both in the professional and in the lay literature. However, no study has tried to examine this issue quantitatively.ObjectiveThe objective of our study was to examine possible systematic biases in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Most available games for health professionals’ education have not passed through an objective validation process, and many of the published studies on the field are biased [59]. So, there is a great need of good quality studies which can provide solid evidence to support the fast-growing science of games for health.…”
Section: Discussionmentioning
confidence: 99%
“…Most available games for health professionals’ education have not passed through an objective validation process, and many of the published studies on the field are biased [59]. So, there is a great need of good quality studies which can provide solid evidence to support the fast-growing science of games for health.…”
Section: Discussionmentioning
confidence: 99%
“…Few articles examine serious games used exclusively by under-, postgraduate medical students, medical doctors, and allied health 5 7 8 11 16 . One review article examined video games and publication trends of the medical literature, but it focused on the possible biases of the researcher’s attitudes toward video games 17 . We did not find a review article that examines the trends of the use of serious games for the education of health professionals, using publication metadata.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the difficulty in defining and naming terms may also be due to researchers’ extant biases and attitudes toward commercial games. Published studies concerning video games from public health, pediatrics, psychiatry, and psychology perspectives appear to have become less positive over time, and studies having a positive focus are more likely to be found in journals with a low impact factor ( 33 ). Reviews of the therapeutic effects of video games usually conflate commercial games and custom-designed games or gamified interventions, making it difficult to compare interventions and draw conclusions about the potential benefits of popular commercial video games.…”
Section: Improving Methodological Practicementioning
confidence: 99%